1976
DOI: 10.1111/j.1365-2265.1976.tb03876.x
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine Potentiation of Gastric Acid Secretion in Cats

Abstract: Bromocriptine administered both orally and intravenously potentiated gastric acid secretion in response to submaximal pentagastrin stimulation in cats. Bromocriptine did not increase the maximum acid secretion in response to pentastrin, not did it stimulate basal acid secretion. Potentiation was observed in normal and vagotomized animals which precludes involvement of the vagi in the response. The mechanism of action of this compound on the stomach does not appear to be mediated through stimulation of dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…High doses of bromocriptine and lergotrile, which stimulate dopamine receptors in the periphery as well as in the central nervous system, reduce gastric acid secretion in the rat (Szabo, 1979), whereas lower doses have an opposite effect both in man (Caldara et al, 1978b) and in the cat (Hirst et al, 1976). The lack of changes in gastric acid secretion in normal volunteers after ibopamine is not easily explained.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…High doses of bromocriptine and lergotrile, which stimulate dopamine receptors in the periphery as well as in the central nervous system, reduce gastric acid secretion in the rat (Szabo, 1979), whereas lower doses have an opposite effect both in man (Caldara et al, 1978b) and in the cat (Hirst et al, 1976). The lack of changes in gastric acid secretion in normal volunteers after ibopamine is not easily explained.…”
Section: Discussionmentioning
confidence: 94%
“…It was shown that dopamine infusion, a drug which does not cross the blood-brain barrier, inhibits gastric acid secretion in man (Caldara et al, 1978a;Valenzuela et al, 1979), while either a decrease or no changes were reported in the animal, possibly due to the different doses employed (Hovendal et al, 1982;Valenzuela & Grossman, 1976). High doses of bromocriptine and lergotrile, which stimulate dopamine receptors in the periphery as well as in the central nervous system, reduce gastric acid secretion in the rat (Szabo, 1979), whereas lower doses have an opposite effect both in man (Caldara et al, 1978b) and in the cat (Hirst et al, 1976). The lack of changes in gastric acid secretion in normal volunteers after ibopamine is not easily explained.…”
Section: Discussionmentioning
confidence: 94%
“…Little is known of the effects of dopamine on gastric and pancreatic secretions. Dopamine infusion has been reported to reduce submaximal pentagastrinstimulated acid secretion in the dog (Valenzuela and Grossman, 1976), but not in the cat (Hirst et al, 1976). Pancreatic secretion was increased by dopamine administration in the dog (Hashimoto et al, 1971;Valenzuela and Grossman, 1976;Bastie et al, 1977).…”
mentioning
confidence: 99%